Spotlight on ORNAC Members: AN INTERVIEW WITH ERIN ROBERTSON RN, BSCN(HONS), CPN(C). - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2014)
Erin Robertson is a Perioperative Registered Nurse working as the Nurse Clinician in Perioperative Services (Operating Room, Elective Outpatient Surgery and Endoscopy) at Mount Sinai Hospital in Toronto, ON. Erin completed the Perioperative Nurse course in 1999 and worked in the Surgical Suites at Kingston General Hospital for three years prior to moving to Toronto. She then spent nine years as a staff nurse in the OR and one year as the patient flow coordinator prior to taking on her current role. During her time at Mount Sinai Erin has completed her post RN BScN (with honours) and is currently taking her Masters of Nursing: Leadership in Education and Health Policy. Erin is an active member of periOperative Registered Nurses of Greater Toronto (ORNGT) and serves as the program convener. Erin lives in Toronto with her husband and two boys.